Representing Autism: A Sociological Examination of Autism Advocacy - McGuire, Anne (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
This paper explores how the cultural phenomenon of autism is being structured by autism advocacy work in the contemporary West. Drawing on recent work in the field of disability studies, I analyze critically the social significance and productive effects of advocacy campaigns that represent autism as a life-threatening pathology.